2020
DOI: 10.3389/fphar.2020.00386
|View full text |Cite
|
Sign up to set email alerts
|

Trichomicin Suppresses Colorectal Cancer via Comprehensive Regulation of IL-6 and TNFα in Tumor Cells, TAMs, and CAFs

Abstract: Trichomicin, a small-molecule compound isolated from fungi, has been identified with bioactivity of antitumor. In this study, a colon cancer subcutaneous mice model was used to evaluate the antitumor effects of Trichomicin in vivo. Treatment with Trichomicin significantly inhibited tumor growth in a xenograft mouse colon cancer model. The underlying molecular mechanism has also been investigated through the quantification of relevant proteins. The expression levels of IL-6 and TNFa were reduced in tumor tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…(4). CIS (MedChemExpress, Monmouth Junction, NJ, USA, 3 mg/kg, dissolved with 0.5% sodium carboxymethyl cellulose (CMC‐Na, MedChemExpress, Monmouth Junction, NJ, USA) according to manufacturer’s instructions) was administered twice a week for a total of five times 55 . (5).…”
Section: Methodsmentioning
confidence: 99%
“…(4). CIS (MedChemExpress, Monmouth Junction, NJ, USA, 3 mg/kg, dissolved with 0.5% sodium carboxymethyl cellulose (CMC‐Na, MedChemExpress, Monmouth Junction, NJ, USA) according to manufacturer’s instructions) was administered twice a week for a total of five times 55 . (5).…”
Section: Methodsmentioning
confidence: 99%
“…99 The macrophages within the tumor microenvironment also produce increased levels of antiangiogenic cytokines such as IL-6. 100 In order to understand the effects of MGF-AuNPs on macrophages, we have investigated the expression of macrophage polarizing cytokines such as IL-12, IL-10, IL-6, and TNF-α upon treating RAW 264.7 macrophages with MGF-AuNPs. In RAW 264.7 macrophages, which were treated with MGF-AuNPs, our experimental findings conclusively demonstrated elevated levels of anti-tumor cytokines such as IL-12 and TNF-, while reducing the levels of pro-tumor cytokines such as IL-10 and IL-6 (Figure 12A, D).…”
Section: Mgf-aunps But Not S-aunps Polarize Macrophages To Anti-tummentioning
confidence: 99%
“…Trichomicin is a small molecule compound with new structure isolated from Trichoderma harzianum ( T. harzianum ) in our laboratory ( Zhu et al, 2020 ). Early in vitro studies confirmed that Trichomicin has significant anti-inflammatory and anti-tumor activities, and inhibits the growth of colon tumor ( Qi et al, 2011 ; Zhao et al, 2020 ). Furthermore, our laboratory also used the anti-inflammatory model to screen the new structure small molecule compound 1487B.…”
Section: Introductionmentioning
confidence: 99%